2016
DOI: 10.18632/oncotarget.7191
|View full text |Cite
|
Sign up to set email alerts
|

Selective brain penetrable Nurr1 transactivator for treating Parkinson's disease

Abstract: Parkinson's disease (PD) is one of the most common movement disorders, and currently there is no effective treatment that can slow disease progression. Preserving and enhancing DA neuron survival is increasingly regarded as the most promising therapeutic strategy for treating PD. IRX4204 is a second generation retinoid X receptor (RXR) agonist that has no cross reactivity with retinoic acid receptors, farnesoid X receptor, liver X receptors or peroxisome proliferator-activated receptor PPARγ. We found that IRX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 45 publications
0
33
0
3
Order By: Relevance
“…24,25 IRX4204, a second-generation RXR agonist, promotes the survival of dopaminergic neurons in mesencephalic cultures in a dose-dependent manner and attenuates neurochemical and motor deficits in a rat PD model. 26 These findings led to the development of a phase 1 clinical study of this agonist. 27 The complexity of the retinoid signaling pathways is further demonstrated by the relation of RXR with vitamin D: vitamin D binds to the vitamin D receptor that dimerizes with RXR.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 IRX4204, a second-generation RXR agonist, promotes the survival of dopaminergic neurons in mesencephalic cultures in a dose-dependent manner and attenuates neurochemical and motor deficits in a rat PD model. 26 These findings led to the development of a phase 1 clinical study of this agonist. 27 The complexity of the retinoid signaling pathways is further demonstrated by the relation of RXR with vitamin D: vitamin D binds to the vitamin D receptor that dimerizes with RXR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, stimulation of RXR by synthetic RXR ligand LG100268 and RXR-Nurr1 ligand XCT0139508 in rat dopaminergic cell cultures protected against oxidative stress induced by 6-OHDA and hypoxia; however, RXR expression alone could not protect the cells when treated with kainic acid and hydrogen peroxide; rather, neuroprotection against these was selective to Nurr1-expressing cells, still implicating RXR as its dimerization partner [129]. Notably, when administered to rats treated with 6-OHDA, IRX4204, a selective RXR agonist, and bexarotene, a cancer drug that binds to Nurr1-RXR heterodimers, attenuated the behavioral and neurochemical deficits in that PD model [130, 131]. Bexarotene also restored signaling by Ret, the canonical GDNF receptor, in mesencephalic mouse neurons overexpressing α-synuclein, suggesting that activation of RXR-Nurr1 may counteract the effect α-synuclein in PD [132, 133].…”
Section: N-3 Pufas and Parkinson’s Diseasementioning
confidence: 99%
“…However, none of these studies used an inflammation‐based therapy and microglia‐NSC combined approach to modify the detrimental host brain environment. Furthermore, recent studies have shown that Nurr1‐activating compounds, Nurr1 modulators, and Nurr1‐based cell transplantation have certain therapeutic effects on PD animal model . However, most of these studies ignored the interference of the hostile and inflammatory environments, which could seriously damage the outcome of these treatments.…”
Section: Discussionmentioning
confidence: 99%